Perfect Ageing: Meditation and Pragmatic Hindu View - Gaur, Vidhu (International Journal of Psychosocial Rehabilitation, 2020)
In dealing with any social organization, we must inquire into the essential ideas, on which it is founded, the conception of life which inspired it, and the forms which these ideas of life assume. The inspiring ideas are always larger than the historical forms which embody them. The Hindu view of the individual and his relation to society can be best brought out by a reference to the synthesis and gradation of (1) the fourfold object of (parusartha): desire and enjoyment (kama), interest (artha), ethical living (dharma), and spiritual freedom (moksa); (2) the fourfold order of society (varna): the man of learning (brahmin), of power (kshatriya), of skilled productivity (vaishya), and of service (sudra); and (3) the fourfold succession of the stages of life (ashrama): student (brahmachari), householder (grihastha), forest recluse (vanprastha), and the free supersocial man (sannyasin). By means of this threefold discipline the Hindu strives to reach his destiny, which is to change body into soul, to discover the world’s potentiality for virtue, and derive happiness from it. It used to be said that God created the universe in order that He might apprehend Himself. Whatever we may feel about it, it is beyond question that the world exists in order that we may apprehend ourselves, attaining our full selfhood through response to whatever in it corresponds to the developing personality. The approach to this goal must not be too sudden and immediate for all individuals. It has to be reached through a progressive training, a gradual enlarging of the natural life accompanied by an uplifting of all its motives, The rule, the training, and the result differ with the type of the individual, his bent of life and degree of development. Life is just too complex for an ideal simplicity. (Radhakrishnan, 1988)